2012
DOI: 10.1021/ja211266m
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Electrode Performance of Ge through Ge@C Core–Shell Nanoparticles and Graphene Networks

Abstract: Germanium is a promising high-capacity anode material for lithium ion batteries, but it usually exhibits poor cycling stability because of its huge volume variation during the lithium uptake and release process. A double protection strategy to improve the electrode performance of Ge through the use of Ge@C core-shell nanostructures and reduced graphene oxide (RGO) networks has been developed. The as-synthesized Ge@C/RGO nanocomposite showed excellent cycling performance and rate capability in comparison with G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
426
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 436 publications
(444 citation statements)
references
References 36 publications
14
426
1
3
Order By: Relevance
“…In addition, Germanium (Ge) has been intensively studied recently due to its 400 times faster lithium diffusivity and 104 times higher electrical conductivity than the commonly and widely studied silicon [18][19][20]. This makes it a promising candidate for composites with SWCNTs for use as a flexible anode.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Germanium (Ge) has been intensively studied recently due to its 400 times faster lithium diffusivity and 104 times higher electrical conductivity than the commonly and widely studied silicon [18][19][20]. This makes it a promising candidate for composites with SWCNTs for use as a flexible anode.…”
Section: Introductionmentioning
confidence: 99%
“…Some progression on composite anodes based on graphene and germanium (i.e., alloy material), MFe 2 O 4 (M = Co, Ni, Cu) and M x S y (M = Sn, Sb, In) were reported in 2012. Different amounts of RGO were combined with carbon-coated [ 181,182 ] or uncoated [ 183,184 ] Ge nanoparticles and tested as anode material. Although a large 1 st cycle irreversibility was present in most of the cases, the quite stable cycling behavior and the reasonably low delithiation voltage, with a plateau at about 0.…”
mentioning
confidence: 99%
“…Ge, Ge-porous Carbon, Ge-CNT, and Ge-CNF Composites Another approach to improve the reversibility of LIB anodes based on Ge is the use of carbon coating and porous carbon to act as structural buffers during Li insertion/deinsertion, which was demonstrated by a significant number of reports [74,[80][81][82][83][84][85][86]. For example, a recent study reported a facile method to produce Ge/carbon nanostructures by carbon coating and reduction of the Ge oxide precursor, forming two different self-assembled nanostructures; clustered and non-clustered structures [82], as shown in Figure 5(b).…”
Section: Carbon Coatedmentioning
confidence: 99%